2017
DOI: 10.1038/s41598-017-02201-5
|View full text |Cite
|
Sign up to set email alerts
|

The perceived stability of scenes: serial dependence in ensemble representations

Abstract: We are continuously surrounded by a noisy and ever-changing environment. Instead of analyzing all the elements in a scene, our visual system has the ability to compress an enormous amount of visual information into ensemble representations, such as perceiving a forest instead of every single tree. Still, it is unclear why such complex scenes appear to be the same from moment to moment despite fluctuations, noise, and discontinuities in retinal images. The general effects of change blindness are usually thought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
106
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(120 citation statements)
references
References 35 publications
11
106
3
Order By: Relevance
“…The reason we find serial dependence rather than a negative aftereffect is likely because of (1) the brief exposure duration in our experiments (adaptation studies generally expose observers to an image for many seconds or even minutes), and (2) the long inter-stimulus intervals in our experiments, as well as the fact that (3) each trial had a random expression, which would tend to wash out adaptation and reduce negative aftereffects. With that in mind, both adaptation and serial dependence are likely operating here and in previous studies, albeit with different time courses, as found in the orientation domain Fritsche et al, 2017;Liberman et al, 2016;Manassi et al, 2017). In addition, adaptation and positive serial dependences share some similarities.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…The reason we find serial dependence rather than a negative aftereffect is likely because of (1) the brief exposure duration in our experiments (adaptation studies generally expose observers to an image for many seconds or even minutes), and (2) the long inter-stimulus intervals in our experiments, as well as the fact that (3) each trial had a random expression, which would tend to wash out adaptation and reduce negative aftereffects. With that in mind, both adaptation and serial dependence are likely operating here and in previous studies, albeit with different time courses, as found in the orientation domain Fritsche et al, 2017;Liberman et al, 2016;Manassi et al, 2017). In addition, adaptation and positive serial dependences share some similarities.…”
Section: Discussionmentioning
confidence: 78%
“…Participants then saw a test screen containing a random adjustment face, which they modified by scrolling through the continuous expression wheel to match the target expression. After picking a match expression, participants saw a 1000-ms noise mask followed by a 1000-ms fixation cross before the next trial began Cicchini et al, 2014;Cicchini, Mikellidou, & Burr, 2017;Corbett et al, 2011;Liberman et al, 2014;Manassi et al, 2017). In Experiment 3, serial dependence was not ethnicity selective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our perception depends on past experiences 1 . Serial dependence -how our current estimates are biased towards previous ones -has been described experimentally using many different paradigms [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] . In particular, paradigms including delayed-estimations of different visual features 2 , such as orientation 9,11,15 , numerosity 19 , location 3,20,21 , facial identity 22 or body size 13 .…”
Section: Introductionmentioning
confidence: 99%